The correlation between sports results in swimming and general and special muscle strength - Lubkowska, Wioletta; Wiażewicz, Aleksander; Eider, Jerzy (Journal of Education, Health and Sport, 2017)
Introduction. Swimming as a sport encompasses various styles and distances (from 50 up to 1,500 meters). The correlation between sports results and general/special muscle strength seems unquestionable. Aim. The purpose of this paper is to answer the question related to maintaining the proportion between muscle strength development (which depends mainly on land-based trainings) and endurance trainings in water. Material and methods. The study covered 14 leading swimmers from MKP Szczecin who specialized mainly in short and medium distances; they were members of the national senior and junior teams in the 2013/14 training year. The general strength tests were conducted at the beginning and at the end of the winter and summer preparatory periods. The following tests were performed: bench-pressing, pull-ups and bar dips. At the end of the main research period, a thrust test was conducted on land (on a swim bench), as well as a thrust test in the water. Results. All participants demonstrated progress in results between the summer season and the winter season. The range of training loads was higher in the summer due to the length of preparation (by about 100%). The individual progress was, however, very varied. Conclusions. The level of sports progress achieved by individual swimmers was greatly diversified. The relatively high level of general and special strength in the tested swimmers was linked to their need to display these motor skills while swimming. Subjects who showed the greatest progress in the general and special strength trials, displayed the biggest improvement in their swimming performance during the competition season. Swimmers with a fairly high level of strength, but a moderate sports level should analyze and improve their swimming technique. Subjects whose progress in general and special strength tests was the least significant, should try and achieve progress by developing other technical and coordination skills.